Local Knowledge Analysis for Animal Water Sustainability at Ngerong Cave in Rengel Village, Rengel Subdistrict, Tuban Regency – East Java - Wahyu Handayani (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2017)
Ngerong Cave is a cave with a length of 1.8 km is located in the center of Rengel District. This cave is a unique cave because of it flowing river inhabited millions of Bader Bang Fish (Punctius javanicus) from small to more than 70 cm long, hundreds of big fish arengan (Morelius/Labeo chrysophekadion), dozens of bulus/labi- labi with a diameter of more than one meter, and millions of bats that live on the roof of the cave. The preservation of these animals (especially aquatic animals) is inseparable from the myths that circulate in the community about the sacred nature of the place and its animals. The main myths in circulation are: whoever eats or brings home fish from the river in Ngerong Cave will be infected with a disease that never healed even will cause a mysterious death. This is a continuation of the myth that the invisible creature wich live in Ngerong Cave will not be willing if their pets are harassed by humans and will pursue the man by asking for his life. Because of the myth, the preservation of river animals in Ngerong Cave can be maintained and protected from human disturbance. Research on the benefits of myths in preserving aquatic animals in Ngerong Cave has a goal to explain to the scientific world that the myth (as one study of cultural anthropology) has a very big role in maintaining environmental sustainability. In general, the methodology of this study used a mixing method in the form of qualitative methods with data analyzed from literature studies and field studies, methods adapted to the focus of the problems studied. In this study, the results obtained depict in depth cultural events in the study area.